Sosialisasi penulisan surat dinas di Kantor Dinas Perhubungan Kota Bekasi - yusril dava bayu (Abdimas Siliwangi, 2023)
Official/Formal letters already have clear formats and rules in writing, but in reality, mistakes are often found that are made repeatedly. Writing that is done in a template or following a previous writing pattern is one of the reasons why the error keeps repeating itself. The purpose of the official letter-writing training at the Department of Transportation Bekasi City is to provide an understanding of the department transportation employees, especially the administrative staff, about writing good and correct official letters. This community service program activity was carried out for two days, namely on 07 April 2023 which took place at the Department of Transportation Bekasi City Office. The administrative Staff of the Department of Transportation who participated in this official letter-writing training totaled 25 people. The socialization method used is direct lectures and questions/answers. Based on the initial identification through the writing process, the writing form of the activity participants still found many errors in spelling and sentences that were less effective, meaning that it is necessary to increase the application of Indonesian spelling in accordance with the current spelling. During the training, the participants and the community service implementation team conducted an evaluation and asked questions directly about the material that had been presented. Then, activity participants understand the mistakes and know the corrections have been submitted by the abdimas team so that participants can properly and correctly compose official letters in accordance with the General Guidelines for Indonesian spelling